Not just understudies: The dynamics of short‐term leadership - Farquhar, Katherine W. (Human Resource Management, 1995)
Contrary to the stereotype that the period between CEOs is a hiatus, interim and acting executives serve during an important strategic window. A model is presented to illustrate the dynamics of short‐term leadership, including the precipitating circumstances for the temporary administration, the tasks of short‐term leadership, and the moderating factors seen to affect the selection and success of the next chief executive. Researchers and practitioners are urged to consider more carefully the potential that a well‐managed interregnum has to repair damage from a traumatic departure, buffer between administrations, and prepare the organization to accept and work with new leadership. © 1995 by John Wiley & Sons, Inc.